Urban remote sensing applications: A collection of Malaysia case study - Mohd. Noor, Norzailawati; Abdullah, Alias (IIUM Press, 2017)
Telecommuting has been recognized and promoted as a strategy for alleviating traffic congestion in urban areas, especially reducing rush-hour traffic. Substantial evidence in the literature suggests that Telecommuting is more suited to women who when compared to men, experience more work/non-work role conflict and more career interruptions. This research is being carried out at a time when the city of Kuala Lumpur is still experiencing traffic congestion, increased reliance on privately owned vehicles and a dwindling public transportation ridership.